Evaluation of Anesthetic Drugs and Disposables Wastage in the Operating Room: Cross Section Study - Pooja Giriyapur; Ravi Madhusudhana; Annadaneshwari B B (Innovative Journal of Medical and Health Sciences, 2022)
Context: The cost of anesthetic technique has three main components that is disposable supplies, equipments, and anesthetic drugs. More often they are overprescribed or wastage can happen. Aim: To estimate the amount of anesthetic drug wastage in operation theatres (OT) and to determine the amount of disposable wastage in OT’s conducted for surgeries. Settings and Design: Cross section study conducted in 12 operation theatre room of tertiary care hospital. Materials and methods: Drug wastage was considered as the amount of drug left unutilized in the syringes/vials after completion of case. An estimation of cost and wastage of drug was made. Results: The study revealed that out of 34 total participants, majority of them were females (64.7%), with mean age of study participants is 45.44 ± 19.6 years. Drug wastage varied from 2.9%(adrenaline) to 100%(atropine), with an overall mean wastage rate of 54%.In addition to the drugs, a high amount of waste was the syringes (24.5%). With consumption rate of 95.4%. Conclusions: Judicious use of drugs and disposables with appropriate interventional measures can effectively decrease this cost. Key words: Anesthetic drugs, Cost, Operation theatre, Wastage